PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI SMAN 2 PADANG - Ananda, Melatika (Departemen Matematika, 2024)
Students of class XI SMAN 2 Padang FY 2023-2024 will be the subjects in this study, which aims to compare the effectiveness of direct learning effect on problem solving ability and PBL model. The research design used in the study is a quasi-experimental design. By using Simple Random Sampling, the sample class was selected. Compared to direct learning, PBL produced better scores on the final exam given to both sample classes.Keywords– Problem Solving ability, Problem PBL, Direct Learning